2022
DOI: 10.1007/s11011-022-01035-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms underlying the association between type II diabetes mellitus and cognitive dysfunction in rats: a link between miRNA-21 and Resveratrol’s neuroprotective action

Abstract: Cognitive impairment is considered as a typical feature of neurodegenerative diseases in diabetes mellitus (DM). However, the exact link between cognitive dysfunction and diabetes mellitus is still vague. This study aims to investigate some of the mechanisms underlying cognitive impairment that associates diabetes mellitus and insulin resistance. We investigated the role of resveratrol as well on cognitive function in experimentally induced type 2 diabetes highlighting on its influence on the expression of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Resveratrol, a polyphenol phytoalexin, has been studied for its potential therapeutic effects in diabetes (El-Sayed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol, a polyphenol phytoalexin, has been studied for its potential therapeutic effects in diabetes (El-Sayed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a polyphenol phytoalexin, has been studied for its potential therapeutic effects in diabetes (El‐Sayed et al., 2022 ). Our results demonstrated that treatment with resveratrol reversed the reduction in the mRNA expression of SOD , CAT , GPx1 , Nrf2 , and NQO1 induced by high glucose in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and reduced antioxidant defenses create a deleterious combination that disrupts cell function and damages cells, leading to the loss of synapses and cell death. At the same time, hyperglycemia can also activate a variety of signaling pathways, leading to increased ROS production and insulin resistance [15].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol exerted beneficial action on age-related alterations, as senile sarcopenia, by promoting peroxisome proliferator-activated receptor-gamma coactivator 1α (PGC1α) expression and myocyte differentiation by miR-21 and miR-27b upregulation and a decrease of miR-133b, miR-30b, and miR-149 levels [ 83 ]. In addition, the resveratrol-induced miR-21 upregulation alleviated cognitive impairment due to insulin resistance and diabetes in mice [ 84 ]. The link between saturated fatty acids (SFA) and poor health outcomes and metabolic disorders [ 85 ] is already well established; additionally, it is reported that SFA effects on human health could also depend on their influence on miRNAs [ 86 ].…”
Section: Food-derived Nutrients As Mirna Regulators In Chronic Diseasesmentioning
confidence: 99%